2020
DOI: 10.1016/j.foodqual.2020.103891
|View full text |Cite
|
Sign up to set email alerts
|

Sweet and bitter near-threshold solutions activate cross-modal correspondence between taste and shapes of cups

Abstract: Sweet and bitter near-threshold solutions activate cross-modal correspondence between taste and shapes of cups. Food Quality and Preference,

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Many researchers aligned the individual IE (T1R to sweetener) or DS to the edulcorant data including sweetness/bitterness of various sweeteners [ 8 , 10 , 13 , 14 ] or to the threshold values [ 8 , 14 ], but found hardly any linear relationship. In view of these studies, the hard point was a lack of sweetness/bitterness data.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many researchers aligned the individual IE (T1R to sweetener) or DS to the edulcorant data including sweetness/bitterness of various sweeteners [ 8 , 10 , 13 , 14 ] or to the threshold values [ 8 , 14 ], but found hardly any linear relationship. In view of these studies, the hard point was a lack of sweetness/bitterness data.…”
Section: Resultsmentioning
confidence: 99%
“…To date, the tertiary structures of some human sweet and bitter taste receptors (hSTR/hBTR) have been elucidated using computational methods [ 6 , 7 , 8 , 9 , 10 , 11 ], although their functions are not as clear as those of the T1R family in mammals [ 12 ]. All these research results attribute the generation of taste to the hydrogen bond interactions between a sweetener molecule and the specific amino acids in the taste receptors [ 6 , 7 , 8 , 9 , 10 , 11 , 13 , 14 ] within different domains [ 15 , 16 ]. For instance, for hSTR, it was reported that glucose can bind to the Venus fly trap domain (VFTD) and amino-terminal domain (ATD) of the T1R2 and T1R3 [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In such cases, while it may be natural to consider the shape features of the glassware as affecting physicochemical properties of the volatiles in headspace over the glass, it would seem more likely that it is the psychologicallydetermined crossmodal correspondence between taste and shape that is really doing the work in terms of automatically priming taste expectations, especially given research showing that simply varying outer texture of drinking vessel can also bias taste ratings (see Van Rompay and Groothedde, 2019;Van Rompay et al, 2017. There would also appear to be a correspondence between the shape of a coffee cup and the expected taste of the contents (Carvalho and Spence, 2018;Van Doorn et al, 2017; see also Machiels, 2018;Pich et al, 2020) (Note 10).…”
Section: Semantic Associations Between Shape and Tastementioning
confidence: 99%
“…They discovered a relationship between sweet flavors and circular shapes. Moreover, sour and bitter tastes are more closely associated with angular and pointed geometries (Pich et al, 2020). Spence and Ngo (2012) revealed a relationship between strict shapes and higher bitterness and an association between dairy and mint flavors and circular shapes.…”
Section: Literature Reviewmentioning
confidence: 99%